The Intervening of Customer Satisfaction can Improve on Customer Loyalty - Purnama, Chamdan; Fatmah, Dinda; Rahmah, Mirhamida; Hasani, Syaiful; Rahmah, Yusriyah; Rahmah, Zakiyah Zulfa (Westscience Press, 2023)
This study aims to examine and analyze the effect of product differentiation on customer satisfaction, to test and analyze the effect of product differentiation on customer loyalty, to test and analyze the effect of customer satisfaction on customer loyalty and to test and analyze the indirect effect of product differentiation on customers loyalty through customer satisfaction at Balekambang Mojokerto District, East Java. The sample in this study is 110 tourists sampling used in this study is to use the accidental sampling method. Data was collected using a questionnaire that has been tested for validity and reliability. Data analysis used in this study is linear regression analysis with SPSS for Windows version 24. Based on the results of regression analysis, it was found that first product differentiation has a significant positive effect on customer satisfaction. Second, product differentiation has a direct positive effect on customer loyalty. Third, customer satisfaction has a significant positive effect on customer loyalty. Fourth, product differentiation indirectly has a significant positive effect on customer loyalty through customer satisfaction.